2008
DOI: 10.1068/a39179
|View full text |Cite
|
Sign up to set email alerts
|

Who Wants to Leave the Neighbourhood? The Effect of Being Different from the Neighbourhood Population on Wishes to Move

Abstract: This is the author's Post-print version (final draft post-refereeing as accepted for publication by the journal). The definitive, peer-reviewed and edited version of this AbstractLittle attention has been paid to date to the role of the neighbourhood as a factor influencing residential mobility and the residential choice process. The question addressed here is to what extent neighbourhood characteristics (percentage of rented dwellings, low income households and ethnic minorities in the neighbourhood) influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
139
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 140 publications
(151 citation statements)
references
References 47 publications
(65 reference statements)
6
139
2
Order By: Relevance
“…Again, this association is substantially stronger for the native Dutch and the Western immigrants than for the other groups. This difference also holds when differences in background variables are controlled for (Van Ham and Feijten, 2007). This support the idea that ethnic differences in neighbourhood choices are at least partly explained by differences in neighbourhood preferences.…”
Section: Neigbourhood Choice and Ethnic Specificitysupporting
confidence: 70%
“…Again, this association is substantially stronger for the native Dutch and the Western immigrants than for the other groups. This difference also holds when differences in background variables are controlled for (Van Ham and Feijten, 2007). This support the idea that ethnic differences in neighbourhood choices are at least partly explained by differences in neighbourhood preferences.…”
Section: Neigbourhood Choice and Ethnic Specificitysupporting
confidence: 70%
“…Even if we believed that mixed neighbourhoods would have the desired effects, we think that it will be very difficult to create sustainable mixed tenure areas. There is evidence from the Netherlands that people do not want to live in mixed areas, including mixed tenure areas (Van Ham & Feijten, 2008;see also Van Ham and Clark, forthcoming). Also, there is evidence that there is little interaction between tenure groups in mixed tenure neighbourhoods (Atkinson & Kintrea, 1998;Jupp, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Differences in lifestyle make it not very likely that people with different characteristics will develop social relationships. People like to live among people with similar characteristics (Van Ham and Feijten 2008). It is therefore no surprise that the quantitative studies described above showed that homogeneous neighbourhoods score better than heterogeneous neighbourhoods.…”
Section: The Link Between Social MIX and Social Cohesionmentioning
confidence: 99%